Analisis Lereng Tanpa Perkuatan dan Dengan Perkuatan TPT Pada Software Geoslope - Ikhwan, Mohammad (Jurnal Kridatama Sains dan Teknologi, 2024)
Slope stability is a critical aspect in infrastructure planning and development, especially in areas with complex topography such as Jatigede Village, Sumberrejo District, Bojonegoro Regency. Factors such as local geological characteristics, the intensity of rainfall that occurs, and human activities can significantly influence the potential for landslides which can threaten community safety and potentially damage existing infrastructure in the local location. In Jatigede Village, Sumberrejo District, Bojonegoro Regency, there is an area with a slope reaching 62˚ which is classified as a steep slope. This area is the main access route for local communities to carry out daily activities. However, during the rainy season, this steep slope becomes a location prone to landslides, which can disrupt the smooth flow of traffic and pose a danger to local residents. Overall, this research not only aims to improve academic understanding of slope stability, but also to make a real contribution to the development of a more reliable and sustainable planning methodology, which can be applied in infrastructure projects in various regions with similar geotechnical challenges throughout Indonesia with using the Geoslope program and using the Bishop method. From the results of the analysis using GeoStudio 2023 software with the Bishop method without reinforcement, a value with a Safety Factor (FK) of 0.627 was obtained. And coupled with strengthening the retaining wall with a height of 4.5 m and a width of 2 m, a Safety Factor (FK) value of 1.508 was obtained. Indicates that the slope has now reached a safety level that is considered safe